2013
DOI: 10.1002/ncn3.11
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine/cystatin C ratio as a surrogate marker of residual muscle mass in amyotrophic lateral sclerosis

Abstract: Aim: Identification of sensitive surrogate markers that indicate disease progression in amyotrophic lateral sclerosis might be useful in clinical trials and clinical care. Determination of the creatinine/cystatin C (Cr/CysC) ratio eliminates the effect of renal function on serum creatinine levels; therefore, we considered that the ratio might serve as a surrogate marker of residual muscle mass. We studied the Cr/ CysC ratio as a useful surrogate marker of residual muscle mass in patients with amyotrophic later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 24 publications
0
39
2
Order By: Relevance
“…CysC is another marker of renal function, but it is less affected by the muscle mass than Cr . We, therefore, calculated the serum Cr/CysC ratio to minimize the effect of renal function on serum Cr concentrations …”
Section: Methodsmentioning
confidence: 99%
“…CysC is another marker of renal function, but it is less affected by the muscle mass than Cr . We, therefore, calculated the serum Cr/CysC ratio to minimize the effect of renal function on serum Cr concentrations …”
Section: Methodsmentioning
confidence: 99%
“…Then, ADFs in this area might reflect neurodegeneration of muscles involved in respiratory functions. ADFs are said to show neurodegeneration from before appearance of clinical signs such as muscle weakness and muscle atrophy in ALS (10,14). Therefore we analyzed the prognosis of patients without neck flexors muscle weakness nor shoulder abductors muscle weakness at registration and found that the number of patients with ADFs of the cervical-upper limb area who progressed to severe ALS within 3 years were significant large (χ 2 = 4.00, p = 0.045).…”
Section: Discussionmentioning
confidence: 99%
“…The mRS is a marker of severity of ALS (14). In this study, mild ALS was defined as not requiring daily assistance (grades 1 and 2), moderate ALS as requiring daily assistance (grades 3 and 4), and severe ALS as requiring life support such as tubal feeding, gastrostoma, positive pressure ventilation, tracheotomy, and an artificial ventilator (grade 5, Table 1).…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…The ratio serum creatinine/serum cystatin C (SI) has previously been used as a surrogate marker of muscle mass in amyotrophic lateral sclerosis [23], in patients undergoing physical checkups [24], in ICU patients [17], in lung transplant candidates [18], and in type 2 diabetic patients [25]. All these studies have shown a good correlation of this index with muscle mass, as measured by DEXA, CT scan or electric bioimpedance.…”
Section: Discussionmentioning
confidence: 99%